Antecedent Decision To Purchase Fashion Products Through Video Advertising Social Media Platform On The Millennial Generation In Medan City - Nora Anisa Br Sinulingga; Risa Kartika Lubis; Alfin Farma; Juli Megawati Br Silitonga (Institute of Computer Science (IOCS), 2022)
UMKM is an important part of the economy of a country or region, as well as Indonesia (Tambunan, 2013). with the existence of the COVID-19 pandemic, the sustainability of UMKM s is threatened by a decline in demand for fashion products due to changes in consumer purchasing power. One of the efforts to survive is to digitize. One of them by advertising on social media. Social media that is often accessed by the millennial generation is a platform (Tiktok, Facebook, Youtube, Instagram). The purpose of this study was to determine the significant and significant influence of information, entertainment, credibility, and personalization on purchasing decisions for fashion products through video advertising on social media platforms for the millennial generation in the city of Medan. The type of research used is descriptive quantitative. The data that is processed is the result of interviews and distributing questionnaires. Data collection techniques used are Observation, Interview, and Documentation. While the data analysis technique used in this research is data collection either through observation or interviews, data reduction, data presentation, and conclusions. The results of the direct relationship research show that information, entertainment, credcredibility, and personalization have a positive influence on video advertising and purchasing decisions. Video advertising has a negative influence on purchasing decisions. While the results of the indirect research show tinformationtive, entertainment, credibility, and personalization through video advertising have a negative influence on purchasing decisions.